‘’Ah, uhm, yeaaaah, maybe.’’ Developing a New Data Collection Instrument to Explore the Gendered Realisation of Refusals by Young Adult Speakers of Irish English - Eimear O'Riordan; Anne Marie Devlin (Teanga: The Journal of the Irish Association for Applied Linguistics)
Presenting the development of a specifically created data collection tool, the online spoken discourse completion task (OSDCT), this study aims to shed light on how young adult Irish-English speakers aged 20-30 realise refusals and the factors which influence linguistic choice. The novel OSDCT was created using Google Forms and the Mote browser extension. Eight situationally controlled audio prompts eliciting refusals were recorded onto the form. The 18 participants (9 male and 9 female) responded orally to the prompts by recording their own audio response via the Mote browser extension. The use of the OSDCT resulted in more natural responses and facilitated the consideration of both linguistic and paralinguistic features. The oral-based nature of the tool highlighted, in particular, the prominence of (para)linguistic modifiers such as elongations, pauses, tuts and dysfluencies as pragmatic phenomena present in refusals. The results indicate that the social need to avoid threatening face played a greater role than gender in realising the speech act of refusal; however, gender-based differences emerged when the age of the prompter was taken into account.